The Influence of Professional Competence, Organization Support, and Task Commitment toward English Teacher Performance - Akib Akib (Institut Agama Islam Negeri Kendari, 2022)
The aims of this research are to investigate the influence of positive the direct effect of professional competence, organizational support, and task commitment on the English teacher's performance of SMP and MTs in Kendari. The research applied a survey method with a quantitative approach. The data are collected from 95 English teachers who are selected randomly. The collected data are analyzed by using path analysis. The research results indicate that there is a direct influence of positive professional competence, organizational support, and task commitment on the economic teacher's performance. Also, there is a direct influence of the positive professional competence, organizational support towards the task commitment, and a direct influence of the positive professional competence toward the organization support.Keywords: Organizational support; performance; professional competence; task commitment